Morphological characteristics of brain lesions in HIV infection. - L. R. Shostakovych-Koretskaya; K. Y. Lytvyn; Z. O. Chykarenko; T. V. Usenko; V. O. Logvinenko (Medičnì Perspektivi)
Currently, diseases of the central nervous system are a common cause of death of patients with HIV infection. The article presents results of retrospective analysis of etiotropic structure of 186 lethal cases and typical pathological changes of brain tissue of patients aged 21 to 61 years who had confirmed diagnosis of HIV and died of diseases associated with CNS damage in the Municipal infectious hospital in the city ofDnepr(Ukraine) in the period from 2011 to 2016. The most common causes of death in patients with HIV infection and CNS infection were cerebral tuberculosis (75.0%) including co-infection (n = 35) and meningoencephalitis that developed as a result of yeast fungal (15.6%). In the study of neuropathological processes in the autopsy material of the brain tissue of patients with HIV, various multifocal and diffuse morphological changes have been identified that can be presented in this work in the form of 4 groups: 1) Multiple nonspecific changes associated with both direct action of HIV and co-factors : infection, inflammation, hypoxia, etc., 2) Viral-induced vasculitis with hemorrhages, 3) Subacute aseptic encephalitis, 4) HIV-associated opportunistic infections. General pathomorphological changes in brain tissue are revealed that can cause similarities of clinical manifestations, can complicate differential diagnosis of cerebral lesions of various etiologies, and lead to a divergence of pre and postmortal diagnoses.